A New Device for Fine‐Needle Aspiration Cytology Consisting of a Vibrating Linear Resonant Actuator. (1st October 2020) - Taguchi, Atsushi; Kojima, Tsuyoshi; Okanoue, Yusuke; Kagoshima, Hiroki; Hasebe, Koki; Yamamoto, Hirotaka; Hori, Ryusuke
Abstract : Objective: To evaluate the efficacy of a new device for fine‐needle aspiration cytology (FNAC) consisting of a vibrating linear resonant actuator (LRA). Study Design: Prospective clinical study. Methods: The LRA frequency was optimized by visualization of the needle motion using a high‐speed camera. The FNAC device consists of a vibrating motor fixed to the stopper of a 5‐ml syringe and piston. Upon insertion of the syringe needle into a thyroid nodule (with the stopper attached to the syringe piston), sufficient negative pressure with 1‐ml suction was maintained. Subsequently, samples were obtained using vibration generated by an LRA or an eccentric rotating mass (ERM). Surgically resected thyroid specimens from 10 patients were evaluated. The number of follicular groups required for adequate diagnosis and the number of larger follicular groups were counted. Next, 254 thyroid nodules from 187 patients were also evaluated by FNAC. The inadequacy rate was determined, and final cytology was classified according to thyroid Bethesda categories. Results: The optimized LRA frequency was 155 Hz. Both the LRA and ERM devices resulted in sufficient amounts of diagnostic material and achieved low inadequacy rates. The number of large follicular groups obtained was significantly greater with the LRA device compared with the ERM device. Conclusions: The vibrating device using an LRA for thyroid FNAC resulted in sufficient amounts of thyroid follicular groups and achieved low inadequacy rates. In addition, the LRA device allowed for collection of larger follicular groups sufficient to diagnose appropriate thyroid Bethesda categories. Level of Evidence: 2 Laryngoscope, 131:E1393–E1399, 2021